Metal oxide and metal nitride nanostructures for lithium-ion batteries and supercapacitors - Zhu, Changrong (2016)
This thesis summarizes the typical techniques for nanostructured-electrode-material design and their applications in lithium-ion battery and electrical capacitors detailed down to the basic device composites, working mechanism, research history and status and evaluation parameters. Nanostructures are classified into four types regarding their size and dimensions from zero to three dimensions thus be called 0 D, 1 D, 2 D and 3D nanostructures. Advantages and disadvantages are discussed regarding the varied dimensions of the electrode materials. Examples of metal oxides and nitrides are given to demonstrate the principles of the material design. Mechanisms for high energy storage performance are proposed and analyzed. Method to differentiate capacitive and ion-diffusion typed capacitance is introduced to unveil different factors to affect capacitance contribution.